2013
DOI: 10.1007/s00404-013-2987-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological and molecular markers associated with prognosis and treatment effectiveness of endometrial stromal sarcoma: a retrospective study in China

Abstract: Purpose To evaluate the clinicopathological and immunophenotypic characteristics of endometrial stromal sarcoma (ESS) in China.Methods and materialsSeventy-two consecutive ESS cases treated between 1995 and 2009 were retrospectively reviewed.ResultsSixty-three patients received surgical treatment. Forty-one patients underwent pelvic lymphadenectomy. In paraffin-embedded specimens, expression of the following molecular markers was detected: CD10 (27/36), vimentin (37/38), HHF35 (3/32), S-100 (0/25), desmin (2/2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…Because of its rarity and heterogeneous morphological appearance, low-grade ESS (LG-ESS) is often misdiagnosed as a different uterine neoplasm. [ 2 4 ] Accurate diagnoses are not established in some cases until the disease relapse. [ 3 , 5 ] Although immunohistochemistry (IHC) often plays an adjunct role in the differential diagnosis of different uterine mesenchymal lesions, [ 6 ] sensitive and specific IHC markers have not been identified for LG-ESS, and valid data are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Because of its rarity and heterogeneous morphological appearance, low-grade ESS (LG-ESS) is often misdiagnosed as a different uterine neoplasm. [ 2 4 ] Accurate diagnoses are not established in some cases until the disease relapse. [ 3 , 5 ] Although immunohistochemistry (IHC) often plays an adjunct role in the differential diagnosis of different uterine mesenchymal lesions, [ 6 ] sensitive and specific IHC markers have not been identified for LG-ESS, and valid data are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…One meta-analysis suggest that lymphadenectomy bore little prognostic or therapeutic benefit in patients with uterine sarcoma [16]. However, another study showed total hysterectomy with BSO followed by pelvic lymphadenectomy was associated with an improved outcome [17]. Our data found that lymphadenectomy had no effect on both disease free survival (p=0.246) and overall survival (p=0.652).…”
Section: Discussionmentioning
confidence: 55%
“…Often, routine imaging (TVS, MRI) seems unable to discriminate between leiomyoma and ESS; for this reason, preoperative diagnosis is not easy. 6 , 17 This neoplasm can be diagnosed preoperatively through hysteroscopic biopsies or through endometrial curettage. 7 , 18 Intraoperative frozen section seems to have an intermediate diagnostic accuracy; only definitive histopathology examination achieves a good accuracy, thanks to the invaluable contribution of immunohistochemistry investigations.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, this last parameter represents the single most important oncological prognostic factor. 4 , 5 , 7 , 17 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation